Incorporating Malay Communicative and Cultural Values in Discourse: An Analysis of Mahathir Mohamed’s Orations - Alkhirbash, Abdulrahman (Advances in Social Sciences Research Journal, 2024)
The cultural values and beliefs of the Malaysian community play a substantial role in shaping their communication approach and strategies. This study was to investigate how Malay values and beliefs were incorporated in communication in one of the most effective speeches of Mahathir Mohamed as a prominent leader in the Southern East of Asia and how these values were employed to influence his audience. The thematic analysis was used to analyse the selected speech and identify key themes, ideas, and topics that reflected Malay communicative and cultural values including indirectness, politeness, and Islamic beliefs. The findings demonstrated a notable contrast between the way Mahathir communicates and the discourse of indirectness commonly associated with Malay discourse. They showed that Mahathir employed direct language and assertive communicative approach to convey his messages and to avoid confusing his audience. This departure from traditional norms suggests that Mahathir recognizes the importance of clarity and precision in persuasive communication, prioritizing audience comprehension over conformity to cultural expectations. While Mahathir is unlike Malays in terms of indirectness, he employed other Malay communicative values such as referring to Islam principles, rationality and emotionality. He incorporated rationality (akal budi) with emotion (hati budi) to work together to influence his audience.